Ions in solution and their solvation - Marcus, Yizhak (Wiley, 2015)
The book starts with an exposition of the relevant properties of ions and continues with a description of their solvation in the gas phase. The book contains a large amount of factual information in the form of extensive tables of critically examined data and illustrations of the points made throughout. It covers: * the relevant properties of prospective liquid solvents for the ions * the process of the transfer of ions from the gas phase into a liquid where they are solvated * various aspects of the solutions of the ions, such as structural and transport ones and the effects of the ions on the solvent dynamics and structure * what happens in cases where the solvent is a mixture selective solvation takes place * applications of the concepts expounded previously in fields such as electrochemistry, hydrometallurgy, separation chemistry, biophysics, and synthetic methods